2022
DOI: 10.3390/pharmaceutics15010031
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Functions and Therapeutic Applications of α7 Nicotinic Acetylcholine Receptor in Brain Disorders

Abstract: Accumulating data suggest that α7 nicotinic acetylcholine receptors (α7nAChRs) are an important therapeutic target for the treatment of Alzheimer’s disease (AD) and schizophrenia. The homopentameric ligand-gated ion channel α7nAChR consists of five identical α7 subunits that are encoded by the CHRNA7 (cholinergic receptor nicotinic alpha7 subunit) gene. Moreover, α7nAChRs are densely distributed throughout the hippocampus, cortex, and thalamus brain regions, but sparsely in the striatum, forebrain, and medulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Activation of a7nAch receptors has been demonstrated to ameliorate ischemic–reperfusion injury and provide neuroprotection. 32 In addition, we previously reported that tropisetron reduces inflammation and myocardial ischemic–reperfusion injury after heart valve replacement surgery. 11 Moreover, antagonism of 5HT-3 receptors has been shown to have anxiolytic effects on animal models through modulation of the serotonergic system.…”
Section: Introductionmentioning
confidence: 98%
“…Activation of a7nAch receptors has been demonstrated to ameliorate ischemic–reperfusion injury and provide neuroprotection. 32 In addition, we previously reported that tropisetron reduces inflammation and myocardial ischemic–reperfusion injury after heart valve replacement surgery. 11 Moreover, antagonism of 5HT-3 receptors has been shown to have anxiolytic effects on animal models through modulation of the serotonergic system.…”
Section: Introductionmentioning
confidence: 98%
“…28 Great efforts are made to find new treatments for these diseases, and although the potentiation of the cholinergic system will not solve these pathological conditions, until now it is the main pharmacological strategy. 29 Through previous research, we identified caffeine as a new leader that can inhibit AChE and activate both muscle and α7 nAChR. 30 Caffeine behaves as a partial agonist at low micromolar concentrations and as an ion channel blocker at high micromolar concentrations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As stated above, although there are different nAChR having distinct pharmacological profiles, muscle and α7 nAChR, both involved in myasthenic syndromes and in AD, are inhibited by α-bungarotoxin (α-BTX) . Great efforts are made to find new treatments for these diseases, and although the potentiation of the cholinergic system will not solve these pathological conditions, until now it is the main pharmacological strategy …”
Section: Introductionmentioning
confidence: 99%
“…Understanding the scope of expression of nicotinic acetylcholine receptors (nAChRs) within hippocampal interneurons would lend great insight for cognitive therapies used in Alzheimer’s Disease [ 1 , 2 ], Attention-Deficit Hyperactivity Disorder [ 3 ], Autism Spectrum Disorder [ 4 ], and Post-Traumatic Stress Disorder [ 5 ]. The GABAergic interneurons are controlled by nAChRs found on their dendrites, soma, and on the axon terminals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%